Write sec theta - tan theta sin theta in terms of sin theta and cos theta; then simplify if possible. (Leave your answer in terms of sin theta and/or cos theta)? See details for the problem

sin theta - tan theta sin thetasinθtanθsinθ

1 Answer
Apr 3, 2018

Hope this helps

Explanation:

sec theta - tan theta sin theta =(1/(cos theta))-(sin^2 theta)/(cos theta)secθtanθsinθ=(1cosθ)sin2θcosθ
But 1-sin^2 theta = cos^2 theta1sin2θ=cos2θ. Hence
= cos^\cancel(2) theta/(\cancel(cos theta)
sec theta - tan theta sin theta=cos theta